An analysis of replenishment policies for perishable inventory system with postponed demand and multiple vacations. (2016) - Radhamani, V.; Sivakumar, B.; Arivarignan, G.
In this article, we consider a perishable inventory system with postponed demand and single server. The server is allowed to take multiple vacations during stock out period. The demands that arrive during a stock out period or server vacation period either postponed their demand or considered to be lost according to a Bernoulli distribution. The postponed demands are sent to a place called pool and its capacity is finite. When the server is not in vacation and the inventory level is above s, the demands in the pool are selected one by one with FCFS discipline. The waiting time distribution for demands in the pool is derived for both (s, S) and the variable ordering policy. System performance measures for model with variable ordering policy and (s, S) policy are also computed under steady-state case. And these performance measures are used to calculate the total expected cost rate for both policies. Finally, using numerical results, we compare the optimal total cost rate corresponding to two policies and also we compare the expected waiting time of the pooled demands.